Endoscopic mucosal resection with an additional working channel (EMR+) in a porcine ex vivo model: a novel technique to improve en bloc resection rate of snare polypectomy - Knoop, Richard F.; Wedi, Edris; Petzold, Golo; Bremer, Sebastian C.B.; Amanzada, Ahmad; Ellenrieder, Volker; Neesse, Albrecht; Kunsch, Steffen (Endoscopy International Open, 2020)
Background and study aims Recently, a new external additional working channel (AWC) was introduced by which conventional endoscopic mucosal resection (EMR) can be improved to a technique termed “EMR+”. We first evaluated this novel technique in comparison to classical EMR in flat lesions. Methods The trial was prospectively conducted in an ex vivo animal model with porcine stomachs placed into the EASIE-R simulator. Prior to intervention, standardized lesions were set by coagulation dots, measuring 1, 2, 3 or 4 cm.Results Overall, 152 procedures were performed. EMR and EMR+ were both very reliable in 1-cm lesions, each showing en bloc resection rates of 100 %. EMR+ en bloc resection rate was significantly higher in 2-cm lesions (95.44 % vs. 54.55 %, P = 0.02), in 3-cm lesions (86.36 % vs. 18.18 %, P < 0.01) and also in 4-cm lesions (60.00 % vs. 0 %, P < 0.01). Perforations occurred only in EMR+ procedures in 4-cm lesions (3 of 20; 15 %).Conclusions With its grasp-and-snare technique, EMR+ facilitates en bloc resection of larger lesions compared to conventional EMR. In lesions 2 cm and larger, EMR+ has demonstrated advantages, especially concerning en bloc resection rate. At 3 cm, EMR+ reaches its best discriminatory power whereas EMR+ has inherent limits at 4 cm and in lesions of that size, other techniques such as ESD or surgery should be considered.